An Evaluation on the Place of Mathematical Knowledge Between Bodily Form and Metaphysics - Karakaya, Vatan (BEYTULHIKME FELSEFE CEVRESI, 2022)
The primary purpose of this study is to evaluate the place of mathematical knowledge between the field of physical knowledge and the field of metaphysical knowledge. The state of being's creation necessitates the knowledge of being in terms of being, which is metaphysical knowledge. The fact that matter comes into existence through form as pure power and possibility is called body in the sensible realm. The basis of our research is how the images of the body world are transformed into information through external and internal senses. In general, in the world of bodies, the quantitative domain of the non-sensible information field, which is formed by its images, can be described as mathematical knowledge. Therefore, it turns out that mathematical knowledge is formed by the quantities of the realm of existence after the creation of existence, and that there is a human competence between metaphysics and the sensible world. Another subject that the study focuses on is to explain how metaphysics, mathematics, and sensible knowledge are perceived in different civilization basins and which aspects are discussed in the history of philosophy. First, the fact that the existence formed by the theories of Plato and Aristotle in the ancient Greek civilization basin is the subject of knowledge is briefly discussed. Then, the perspective of existence and knowledge of the peripatetic thought tradition in Islamic civilization is explained with the main lines and again, the theory of existence and knowledge of kalam, which is one of the Islamic thought traditions, is mentioned.
Keywords: Matter; form; metaphysics; knowledge; mathematical knowledge; Philosophy